The money lenders [videorecording] the World Bank and International Monetary Fund a global report - Crawford, Tom.; Kindy, Peter; Richter, Robert ([S.l.] Richter Productions, 1991)
Documents transactions with World Bank and IMF. Also tackles the social and economic conditions of countries with debts to the World Bank.
VHS.
Keywords: World Bank; International Monetary Fund; Banks and banking; Bolivia -- Economic conditions; Brazil -- Economic conditions; Ghana -- Economic conditions; Philippines -- Economic conditions; Thailand -- Economic conditions